MiR-216a-5p protects against high glucose-induced HMC injury by targeting the HMGB1/RAGE signaling pathway - Zhang, Juan; Zheng, Xiyin; Zhang, Hong; Chen, Juan (Frontiers in Endocrinology, 2025)
The pathogenesis of diabetic nephropathy (DN), a primary microvascular complication of diabetes and a leading cause of end-stage renal disease, remains incompletely understood. This study delved into the role and underlying mechanisms of miR-216a-5p in the development of DN. Our initial findings revealed a lower serum level of miR-216a-5p in DN patients (P < 0.05). In vitro experiments, in which high glucose concentrations were used to stimulate human mesangial cells (HMCs), demonstrated a significant increase in the protein level of high mobility group box 1 (HMGB1) and a marked decrease in miR-216a-5p expression (all P < 0.05). Subsequent cell experiments showed that miR-216a-5p enhanced HMC viability, stimulated cell proliferation and inhibited cell apoptosis. It also alleviated the fibrosis and inflammatory response of HMC cells under high glucose conditions (all P < 0.05). A dual-luciferase reporter assay confirmed a direct binding between HMGB1 and miR-216a-5p. Moreover, miR-216a-5p suppressed the expression of HMGB1, as well as its receptor for advanced glycation end products (RAGEs). In summary, miR-216a-5p protects against high glucose-induced HMC injury by targeting the HMGB1/RAGE pathway, providing a new perspective for the subsequent treatment of DN.